2015
DOI: 10.7314/apjcp.2014.15.24.10923
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histopathological Characterization of Prostate Cancer in Saudi Patients by Conventional and 2005 ISUP Modified Gleason Systems

Abstract: Background: The aim of this study was to compare the characterization of prostate cancer using the conventional and 2005 ISUP modified Gleason systems. Materials and Methods: The study employed samples from 40 prostate cancer patients with resection, biopsy and RP materials. The majority of cases (95%) comprised adenocarcinoma of the prostate with a modified combined Gleason score of 7 in 20 of the cases (50%). Results: Upgrading of Gleason scores to a score of 7 occurred in more than 45% of the cases. Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the ISUP 2005 mGS and subsequently the ISUP 2014 mGS, the definition of Gleason pattern 3 was further specified, moving some architectural patterns from Gleason pattern 3 to the pattern 4 category, and as a consequence the definition of pattern 4 is expanded, causing a shift of PCa graded as biopsy GS ≤6 towards GS 3 + 4 = 7 After revision of biopsy specimens, upgrading to ISUP 2005 mGS 3 + 4 = 7 occurs in 19–45% of men originally diagnosed with cGS ≤6 The upgrading rate of 30% in the present study is in line with these previous findings. To our knowledge, we are the first to report on a higher GS upgrading rate in men who died of PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ISUP 2005 mGS and subsequently the ISUP 2014 mGS, the definition of Gleason pattern 3 was further specified, moving some architectural patterns from Gleason pattern 3 to the pattern 4 category, and as a consequence the definition of pattern 4 is expanded, causing a shift of PCa graded as biopsy GS ≤6 towards GS 3 + 4 = 7 After revision of biopsy specimens, upgrading to ISUP 2005 mGS 3 + 4 = 7 occurs in 19–45% of men originally diagnosed with cGS ≤6 The upgrading rate of 30% in the present study is in line with these previous findings. To our knowledge, we are the first to report on a higher GS upgrading rate in men who died of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from human reading error, undergrading could have been caused by insufficiencies in the cGS, used to grade the biopsy specimens in the prevalence screening round of the ERSPC Rotterdam (1993–1999). In 2005, the ISUP mGS was adopted Biopsy grading according to the ISUP 2005 mGS tends to decrease the number of GS ≤6 PCa and increase the number of GS 3 + 4 = 7 PCa Although challenged by some, it has been shown that prognostic prediction based on prostate biopsy is more accurate with the ISUP 2005 mGS as compared with the cGS Recently, an updated GS was proposed based on the ISUP consensus conference in November 2014 The ISUP 2014 mGS significantly outperforms the ISUP 2005 mGS in terms of prognostic prediction Hypothetically, part of the PCa deaths with biopsy GS ≤6 at prevalence screening in the ERSPC Rotterdam could be explained by undergrading with the cGS. In the present study, we compared the reclassification rate from biopsy cGS ≤6 to ISUP 2014 mGS 3 + 4 = 7 (grade group 2) at prevalence screening in men who did or did not die of PCa to assess the rate of PCa deaths with GS ≤6 that could be explained by biopsy undergrading.…”
Section: Introductionmentioning
confidence: 99%